Micro-Enterprises and Household Income - Thapa, Ajay (Journal of Nepalese Business Studies, 2008)
This study assesses the role of micro-enterprises in rural poverty reduction and reveals many facts concerning the role of micro-enterprises and some socio-economic and demographic factors in rural poverty reduction in Parbat district. The study has observed a positive role of micro-enterprises in the household income consequently reducing the rural poverty. It has also found that the size of economically active population in the family and secondary or higher level of education of the principal earner of the households also have positive influence in the household income. The Journal of Nepalese Business Studies Vol. IV, No. 1(2007) pp. 110-118